2020
DOI: 10.1159/000511792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Childhood Obesity in Portugal: A Narrative Review of the Literature

Abstract: <b><i>Background:</i></b> The number of childhood obesity cases has been increasing in several countries around the world. In view of all the associated complications at an early stage of child development, it becomes urgent to understand this problem in depth. <b><i>Objective:</i></b> The aim of this work was to describe the prevalence of childhood obesity in Portugal and analyze the trend of its evolution in recent years. <b><i>Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Importantly, as is the case in other Western industrialized societies, Portugal is a highly meat-centric country (Brittin, 2011) and children tend to eat more than the formally recommended levels of animal protein in their diets (Durão et al, 2017). The high consumption of animal products, together with an excessive intake of sugar, are linked to strikingly high levels of child obesity in the country (Durão et al, 2017;Frade et al, 2020). This is also reflected in the typical offer provided in the school meals system, in which the standard practice is to rotate between meat and fish meals every day of the week with little room for plant-based meals.…”
Section: Sustainable Food Transitions In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, as is the case in other Western industrialized societies, Portugal is a highly meat-centric country (Brittin, 2011) and children tend to eat more than the formally recommended levels of animal protein in their diets (Durão et al, 2017). The high consumption of animal products, together with an excessive intake of sugar, are linked to strikingly high levels of child obesity in the country (Durão et al, 2017;Frade et al, 2020). This is also reflected in the typical offer provided in the school meals system, in which the standard practice is to rotate between meat and fish meals every day of the week with little room for plant-based meals.…”
Section: Sustainable Food Transitions In Schoolsmentioning
confidence: 99%
“…The high consumption of animal products, together with an excessive intake of sugar, are linked to strikingly high levels of child obesity in the country (Durão et al. , 2017; Frade et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in China, in 2020, the prevalence of overweight (including obesity) was 19% for children aged 6-17 [4] and, in Europe, in 2018, 19% 15-years-old was either overweight or obese [5]. The data available in Portugal are different, with a prevalence of overweight (including obesity) between 20 to 40% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood obesity has increased in the last 40 years, making it one of the major problems and challenges for public health in advanced societies [ 1 , 2 , 3 ]. Focusing on Portuguese population, previous studies showed that the prevalence of overweight in children and adolescents ranges between 20% and 40%, and obesity between 10% and 15% [ 4 ]. Likewise, the Childhood Obesity Surveillance Initiative (COSI) report for Portugal in 2019 showed a reverse trend in the prevalence of overweight (from 37.9% to 29.6%) and obesity (from 15.3% to 12.0%) in children aged 6 to 8 years-old [ 5 ].…”
Section: Introductionmentioning
confidence: 99%